Time series demand forecasting on NYC taxi dataset - Teh, Timothy Rui Sheng (Nanyang Technological University, 2024)
This project investigates time series forecasting on the NYC Taxi & Limousine Commission (TLC) dataset, aiming to determine how various data preprocessing techniques and feature engineering methods can improve the accuracy of predictions. The TLC dataset, rich in information on taxi demand and supply, serves as a practical case study for evaluating the effectiveness of these advanced forecasting techniques.